NETWORK EFFECT IN THE REGIONAL ECONOMY PROVIDED BY EDUCATION CLUSTERS - Darya-Anna A. Kaybiyaynen (Высшее образование в России)
This article describes the best practices of Tatarstan Republic in creation and development of industrial science and education clusters in the leading universities and their impact on the development of network environment in the regional economy of Tatarstan.